IMPROVING STUDENTS’ TOLERANCE THROUGH THE VCT LEARNING MODEL: A QUASI-EXPERIMENTAL STUDY - Wasis Suprapto; Abdul Ghofur; Delfia Ikhlasiah Rahman; Ulfah Churiwiyah; Dodik Kariadi (Journal of Educational Review and Research, 2025)
Indonesia is a multicultural country. In a multicultural society, tolerance is a crucial aspect of fostering harmony and peace, so students must have a strong understanding of its values. However, the data indicate that intolerant behavior among the public remains significantly high. Inter-ethnic, racial, and tribal conflicts continue to be prevalent, according to the data. Therefore, the best way to overcome this obstacle is by organizing learning that can stimulate students to understand the values of tolerance. This is because students are the next generation, the spearhead in fostering tolerance in a multicultural nation. Consequently, this research aims to apply the VCT (Value Clarification Technique) model to assess its impact on students' knowledge achievement related to tolerance values. This study involved 37 students from one elementary school in Singkawang City, Kalimantan, comprising 20 students in class A (experimental group) and 17 in class B (control group), using a quasi-experimental research design. Data analysis was performed using the independent samples t-test. The research results indicate that the Sig. (2-tailed) value exceeds 0.05, so it can be understood that the VCT model influences students' acquisition of knowledge about tolerance values.